Structure of chorismate synthase from Mycobacterium tuberculosis - Dias, MVB; Borges, J. C.; Ely, F.; Pereira, J. H.; Canduri, F.; Ramos, CHI; Frazzon, J.; Palma, Mario Sergio [UNESP]; Basso, L. A.; Santos, D. S.; de Azevedo, W. F. (Elsevier B.V., 2006)
In bacteria, fungi, plants, and apicomplexan parasites, the aromatics compounds, such as aromatics amino acids, are synthesized through seven enzymes from the shikimate pathway, which are absent in mammals. The absence of this pathway in mammals make them potential targets for development of new therapy against infectious diseases, such as tuberculosis, which is the world's second commonest cause of death from infectious disease. The last enzyme of shikimate pathway is the chorismate synthase (CS), which is responsible for conversion of the 5-enolpyruvylshikimate-3-phosphate to chorismate. Here, we report the crystallographic structure of CS from Mycobacterium tuberculosis (MtCS) at 2.65 angstrom resolution. The MtCS structure is similar to other CS structures, presenting beta-alpha-beta sandwich structural topology, in which each monomer of MtCS consists of a central helical core. The MtCS can be described as a tetramer formed by a dimer of dimers. However, analytical ultracentrifugation studies suggest the MtCS is a dimer with a more asymmetric shape than observed on the crystallographic dimer and the existence of a low equilibrium between dimer and tetramer. Our results suggest that the MtCS oligomerization is concentration dependent and some conformational changes must be involved on that event. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: chorismate synthase; Crystallography; analytical ultracentrifugation; Mycobacterium tuberculosis; shikimate pathway